2020
DOI: 10.1038/s41598-020-77647-1
|View full text |Cite
|
Sign up to set email alerts
|

Controlled elevated temperatures during early-mid gestation cause placental insufficiency and implications for fetal growth in pregnant pigs

Abstract: It is known that pig offspring born from pregnant pigs exposed to elevated ambient temperatures during gestation have altered phenotypes, possibly due to placental insufficiency and impaired fetal growth. Therefore, the objective of this study was to quantify the effect of maternal heat exposure during early-mid gestation, when pig placentae grow heavily, on placental and fetal development. Fifteen pregnant pigs were allocated to thermoneutral (TN; 20 °C; n = 7) or cyclic elevated temperature conditions (ET; 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 52 publications
0
21
0
1
Order By: Relevance
“…Similarly, Zhao et al. [ 22 ] reported lower respiration rates (23 vs. 101 breaths/min) and skin temperatures (30.3°C vs. 36.6°C) in early-to-mid gestating sows kept at TN conditions of 20℃ compared with sows subjected to cyclic HS at 28°C–33℃. Another study reports lower respiration rate and temperature of ear and shoulder in pregnant sows under TN compared with HS [ 4 ].…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…Similarly, Zhao et al. [ 22 ] reported lower respiration rates (23 vs. 101 breaths/min) and skin temperatures (30.3°C vs. 36.6°C) in early-to-mid gestating sows kept at TN conditions of 20℃ compared with sows subjected to cyclic HS at 28°C–33℃. Another study reports lower respiration rate and temperature of ear and shoulder in pregnant sows under TN compared with HS [ 4 ].…”
Section: Resultsmentioning
confidence: 90%
“…Similarly, Liao and Veum [ 25 ] reported that subjecting pigs to cyclic or constant HS in early pregnancy does not influence the parameters tested in our study. In addition, sows housed under TN conditions (20°C) rather than cyclic HS conditions (28°C–33°C) during 40–60 days of gestation were not affected in terms of corpus luteum number and embryo survival rate, but instead a numerical increase was observed in the TN group [ 22 ]. Omtvedt et al [ 8 ] reported no effects on the performance of piglets produced from sows treated with HS during the mid gestating stage.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations